Analysis Of Social Environment, Consumer Perception, Psychology On Consumer Decisions To Use The Services Of PT. Pelindo Multi Terminal Branch Belawan North Sumatera With Consumer Behavior As An Intervening Variable - Fernando Manurung; Nurafrina Siregar; Elfitra Desy Surya (International Journal of Economics, Business and Innovation Research, 2025)
This study seeks to examine the impact of the social environment, customer perception, and psychological aspects on consumer decisions about the services of PT. Pelindo Multi Terminal Branch Belawan, with consumer behavior serving as an intervening variable. This study employs a quantitative methodology, utilizing primary data gathered via structured questionnaires from users of PT. Pelindo Multi Terminal services. We conducted data analysis via structural equation modeling (SEM) to examine direct and indirect correlations among variables. The study's results demonstrate that social environment, consumer perception, and psychological aspects significantly affect consumer behavior, which subsequently influences consumer decisions directly. Furthermore, consumer behavior serves as a mediator in the interaction between independent variables and consumer decisions, with psychological aspects exerting the most significant indirect influence. These findings underscore the significance of comprehending the interplay among social aspects, perceptions, and psychology in influencing consumer choices within the logistics services sector. This research offers a theoretical contribution by synthesizing social and psychological dimensions in consumer decision-making. In reality, these outcomes assist PT. Pelindo Multi Terminal Branch Belawan in enhancing service quality and customer loyalty by monitoring the factors influencing consumer decision-making.